Adapting the determinants of implementation behavior questionnaire to evaluate implementation of a structured low back pain programme using mixed‐methods. Issue 2 (5th April 2021) - Ris, Inge; Schröder, Karin; Kongsted, Alice; Abbott, Allan; Nilsen, Per; Hartvigsen, Jan; Öberg, Birgitta
Abstract: Background and Aims: Best‐practice low back pain (LBP) primary care programmes have been developed based on evidence‐based clinical guidelines and implemented in Sweden and Denmark. The theoretical domains framework (TDF) was utilized in the design of the implementation strategy. Based on the TDF domains, the Determinants of Implementation Behavior Questionnaire (DIBQ) has been developed to evaluate implementation determinants, but its feasibility and validity need to be tested and adapted to study specific contexts. This study aimed to tailor the DIBQ for evaluation of implementation for LBP primary care programmes. The objectives were to (a) translate the DIBQ into Swedish and Danish, (b) adapt the DIBQ into DIBQ‐tailored (DIBQ‐t) to study content validity, (c) test the DIBQ‐t for feasibility, and (d) perform validity testing of DIBQ‐t. Methods: We used a mixed‐methods design. First, forward translation of the DIBQ, then adaptation into DIBQ‐t using qualitative face validity and quantitative content validity was done. Finally, to determine feasibility and construct validity using confirmatory factor analyses, we used data from DIBQ‐t collected after the programmes' 2‐day course. Results: The final DIBQ‐t included 28 items describing 10 of the original 18 DIBQ domains and was considered feasible. A total of 598 clinicians out of 609 responded to the DIBQ‐t, with only 2‰ of the items missing. The confirmatory factor analyses showed a good fit after removing two items with the lowest domain loading. The DIBQ‐t maintained linkage to all domains within the Behavioral Change Wheel. The clinicians' expectations, according to the DIBQ‐t, indicate facilitating determinants outweighing barriers at the initiation of implementation processes. Conclusions: The study resulted in a feasible and valid version of a questionnaire for evaluating clinicians' expectations regarding implementation determinants of best‐practice LBP primary care programmes.